2016
DOI: 10.1016/j.vhri.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Value and Service Quality Assessment of the National Health Insurance Scheme in Ghana: Evidence from Ashiedu Keteke District

Abstract: There is increased value of the NHIS benefit package to subscribers; however, the scheme's responsiveness to the financial needs of health services providers is low. This calls for a review of the NHIS policy to improve financial viability and service quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…Another plausible explanation for the low rate of adjustment is that healthcare providers themselves pre-screen their claims for errors before submitting to the CPC; an exercise that could eliminate omissions and duplications. The finding supports a study by Nsiah-Boateng et al [ 23 ]; however, it contradicts a similar study, where the proportions of claims cost adjusted were 11 and 14% for two NHIA district offices in the Upper East region of Ghana [ 15 ].…”
Section: Discussionsupporting
confidence: 65%
“…Another plausible explanation for the low rate of adjustment is that healthcare providers themselves pre-screen their claims for errors before submitting to the CPC; an exercise that could eliminate omissions and duplications. The finding supports a study by Nsiah-Boateng et al [ 23 ]; however, it contradicts a similar study, where the proportions of claims cost adjusted were 11 and 14% for two NHIA district offices in the Upper East region of Ghana [ 15 ].…”
Section: Discussionsupporting
confidence: 65%
“…Many African countries particularly those in the sub-Saharan Africa (SSA) are at different stages of SHI implementation aimed at achieving UHC [ 9 , 10 ]. It is a general belief that UHC is a panacea for reducing out-of-pocket payment and inequity in access to and utilization of healthcare services [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was fashioned out to address the challenges of the out-of-pocket payment system of paying for healthcare services in the 1990s, popularly referred to as “cash and carry”. The cash and carry system was introduced at that time to recover at least 15% of recurrent expenditure and drugs [ 13 , 18 , 19 ] but it led to increased inequality in healthcare access and preventable deaths [ 10 , 14 , 18 , 20 ]. The NHIS is managed by the National Health Insurance Authority (NHIA), a regulatory body mandated by law to oversee operations of public and private health insurance schemes in the country [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in Africa on the National Health Services have focused on the fragmentation of health care delivery, which hampers the move towards universal coverage [7], benefit of the NHI to subscribers [8], and progress made towards UHC systems of Ghana, South Africa and Tanzania [9]. A study conducted among 216 dentists in Lagos, Nigeria in 2010 indicated that only 62 (28.7%) had good knowledge about the NHI System (NHIS), with the majority 152 (70.4%) viewing the NHIS as a good idea that would succeed if properly implemented [10].…”
Section: Introductionmentioning
confidence: 99%